2021
DOI: 10.2478/bjdm-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perceptions of smile esthetics by dental students

Abstract: Summary Background/Aim: The aim of this study was to investigate in the esthetic perceptions of 2nd grade dental students before and after training. Material and Methods: A total of 16 photographs which contain golden ratio, buccal corridor, midline deviation, incisal embrasure, lip line, midline diastema, dark triangles and smile arc were shown to 78 dental students (33 male, 45 female). Immediately after the training about the smile esthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…At the same time, it was considered acceptable, according to [ 37 , 38 ]. In contrast, 91.0% of students did not find the midline shift attractive [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it was considered acceptable, according to [ 37 , 38 ]. In contrast, 91.0% of students did not find the midline shift attractive [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to those described in [ 10 , 41 ], verifying the impact of structures adjacent to the smile on the perception of upper dental midline deviations in 1 mm. On the other hand, [ 38 , 39 ] studied midline inclinations in an asymmetrical nose and chin and found them to influence perception. Silva and colleagues [ 42 ] observed that laypeople preferred canting of the dental midline in the same direction as the deviation of the nose and chin rather than the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In a case study carried out in 2016, in a young patient with bruxism, a progressive increase in the size and depth of incisal embrasures resulted in a pleasing smile 8 . In older dentition, the incisal edges get blunt with wear and attrition; a younger smile can be given by altering the incisal embrasure forms 9 . Contact points and incisal embrasures are also carefully planned while rehabilitating smiles using direct composite restorations because of their significant influence 10 .…”
Section: Introductionmentioning
confidence: 99%